Intra-urban variations in retail grocery prices - Parker, AJ (Economic & Social Studies, 1974)
Variations in retail grocery prices is an issue that engenders considerable interest in many sections of the community, for a variety of economic and political reasons. Since a substantial proportion of a housewife's weekly budget is spent upon foodstuffs, it is in this area that she is most sensitive to price variations, and, consequently, a strong political platform is the pledge to curb rising prices. In the short term, however, the housewife is less concerned about temporal variations in prices, and more concerned about spatial variations or the differences between one store and another. Since this interest affects the pattern of shopping trips and therefore the demand for travel facilities, variations in retail prices are also of importance to the planner whose function, in part, is to assess and cater for the future magnitude of trip patterns.
Keywords: Grocery prices; Variation; Ireland